(untitled) (REMUNOM, 2026)
Introduction: In the field of mental health, the nurse is responsible for promoting the recovery of individuals experiencing psychosocial distress through the therapeutic relationship, making it essential to master nursing practices to select the actions that will be employed in situations involving patients in psychiatric crisis, particularly regarding the incorrect use of mechanical restraint. Objective: To evaluate the practice of mechanical restraint carried out by nurses as a tool for the recovery of psychiatric patients. Methodology: This is a bibliographic review with an exploratory nature and a qualitative approach, in which a search was conducted for articles published in the last ten years (2016-2025), in Portuguese and English, in the following databases: Latin American and Caribbean Health Sciences Literature (LILACS) and Scientific Electronic Library Online (SciELO), using the following descriptors: nursing, psychiatry, psychiatric patient, mechanical restraint. Of the 752 studies identified in the electronic databases, 79 studies proceeded to full-text reading. After this phase, 10 studies. Results: The findings indicate that the main indications for mechanical restraint are to protect the staff and patient, prevent falls, injuries, and trauma, as well as the predominance of the lack of knowledge among nursing professionals about mechanical restraint protocols and Resolution 427/2012. Conclusion: It becomes essential to have greater coordination among the health care networks involved, with the development of specific and systematic protocols that provide theoretical and practical support for the care of patients requiring mechanical restraint. The importance of ongoing education for nursing professionals and the implementation of public policies is also highlighted in order to ensure the quality of care provided in psychiatric services.